Antifouling waterborne coating, preparation method and application
By adding silicon carbide microline and nano -silicon oxide to the water -based fluorocarbon emulsion resin and water -based acrylic polyurethane resin, the problem of insufficient subjuication of the water -based fluorocarbon emulsion resin has achieved high adhesion and high -polluting water -based coatings. Improve the wear resistance and scratch resistance of the coating.
Patent Information
- Application Number
- CN202411380958.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, the adhesion of the aqueous fluorocarbon emulsion resin is insufficient, resulting in poor stain resistance and smoothness performance of the coating.
Based on the basis of water -based fluorocarbon emulsion resin and water -based polyurethane resin, silicon carbide microfilling and nano -nano -silica oxide are added to form a synergistic effect to improve the adhesion of the paint.
It significantly improves the adhesion of water-based coatings and enhances its anti-fouling and smoothness properties, giving the coating better application prospects in the high-end leather market.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of automotive leather coatings, and in particular to a sewage-proof coating, a preparation method and an application thereof. Background Art
[0002] With the development of the automobile industry, today, consumers have higher and higher demands for the comfort and beauty of car interiors. Therefore, the quality of leather used in car interiors has become one of the selling points that the automobile industry attaches importance to.
[0003] The quality and beauty of automotive leather depend not only on the quality of the leather itself, but also on the coating on the surface of the leather. The coating of automotive leather has many advantages, mainly including:
[0004] (1) Protecting leather: The coating can protect the leather surface and prevent it from being damaged by external factors such as stains, scratches, etc., thereby extending the service life of the leather.
[0005] (2) Improved aesthetics: The coating can make the leather surface smoother, increase the aesthetics of the leather, and enhance the grade of the vehicle.
[0006] (3) Improved comfort: Certain coatings can also provide better touch and comfort, making the riding experience more pleasant.
[0007] (4) Waterproof and breathable: Some advanced coating materials have good waterproof and breathable properties, which can keep the leather dry while allowing the skin to breathe and improve comfort.
[0008] (5) Easy to clean: The coating can enhance the leather's anti-fouling ability, making cleaning easier and reducing the trouble of maintenance.
[0009] At present, most automotive leather coatings are formed by curing water-based paints, and the selection of water-based paint components will affect the various properties of the automotive leather coatings, such as anti-fouling ability, waterproof and breathable ability, smoothness, lifespan, etc. Among them, for higher-end automotive leathers, anti-fouling ability and smoothness are the most important, and have become the main distinguishing points between high-end car interior leathers and mid- and low-end car interior leathers.
[0010] Among them, water-based fluorocarbon emulsion resin, as a resin with extremely strong anti-fouling ability and the ability to improve the smoothness of the coating surface, has become a research hotspot for water-based coatings. However, the cost of water-based fluorocarbon emulsion resin is relatively high. If water-based fluorocarbon emulsion resin is used alone as the main component of water-based coatings, there will still be a problem of insufficient coating adhesion.
[0011] Based on this, prior art 1: Chinese patent application 202111316494.0 discloses a stain-resistant and anti-folding leather product and a preparation method thereof, wherein the stain-resistant and anti-folding leather product comprises a base fabric layer and a polyurethane formulating liquid coated on the surface of the base fabric layer, wherein the polyurethane formulating liquid comprises the following raw materials in parts by weight: 40 to 75 parts of aqueous polyurethane / acrylate composite emulsion, 15 to 30 parts of aqueous fluorocarbon emulsion resin emulsion, 4 to 11 parts of functional powder, 2 to 4.5 parts of cross-linking agent, 0.5 to 2 parts of fluorocarbon surfactant, 3 to 8 parts of hand feeling agent, 4 to 7 parts of zinc oxide antibacterial agent, and 50 to 80 parts of deionized water.
[0012] Prior art 1 uses a water-based polyurethane / acrylate composite emulsion and a water-based fluorocarbon emulsion resin emulsion to form a three-dimensional cross-linked network structure, thereby further improving the wear resistance and stain resistance of the product, and is also beneficial to the adhesion of the polyurethane compounding liquid film; that is, prior art 1 can effectively obtain a water-based coating containing fluorocarbon resin with high adhesion, but it mainly improves the wear resistance and stain resistance of the water-based coating. According to the specification of prior art 1, it can be seen that prior art 1 does not test the adhesion, and it is difficult to confirm that the adhesion of the water-based polyurethane / acrylate composite emulsion in prior art 1 to the water-based fluorocarbon emulsion resin emulsion is improved.
[0013] Based on this, the technical problem to be solved by the present invention is: how to develop a water-based coating with high adhesion and high antifouling ability by targeting the shortcoming of insufficient adhesion of water-based fluorocarbon emulsion resin. Summary of the invention
[0014] One of the purposes of the present invention is to provide a sewage-proof coating, which adds a certain amount of silicon carbide powder and nano-silicon dioxide to a water-based fluorocarbon emulsion resin and a water-based acrylic polyurethane resin to produce a synergistic effect of improving the adhesion of the water-based coating.
[0015] Another object of the present invention is to provide a method for preparing a sewage-proof coating, wherein the prepared sewage-proof coating has excellent anti-fouling ability and excellent adhesion, so that the sewage-proof coating can adhere to the leather surface.
[0016] At the same time, the present invention also provides an application of a sewage-proof coating, which is used as a coating for automotive leather and can bring excellent anti-fouling ability and smoothness, and has excellent wear resistance and scratch resistance, and has excellent market application prospects in the high-end leather market.
[0017] To achieve the above-mentioned purpose, the present invention provides a sewage-proof coating, which comprises, by weight, 20-40 parts of water-based fluorocarbon emulsion resin, 90-110 parts of water-based acrylic polyurethane resin, 0.5-2 parts of silicon carbide micropowder, 0.5-2 parts of nano-silicon dioxide, 0.1-0.3 parts of stabilizer, 0.3-0.6 parts of leveling agent, and 0.3-0.6 parts of defoaming agent.
[0018] Nano-silica particles can produce strong cross-linking effects with polymer molecules. At the same time, due to their small size, they can fill the pores in the coating, making the coating denser; this dense structure can greatly increase the shear force and peeling force of the coating, thereby enhancing the adhesion of the coating.
[0019] Appropriate addition of silicon carbide powder can improve the adhesion of the coating. Unlike irregularly shaped particles, silicon carbide powder can easily roll between each other, which makes the system using silicon carbide powder have lower viscosity and better fluidity. Such characteristics help improve the construction performance of the coating, including sprayability during spraying, thereby improving the uniform coverage and adhesion of the coating.
[0020] The present invention compounds nano-silicon dioxide and silicon carbide powder, and uses silicon carbide powder to improve the fluidity of nano-silicon dioxide during the curing process of water-based paint into a coating, so that the ability of nano-silicon dioxide to fill the pores in the coating is further improved, the density of the coating is increased, and thus the adhesion of the water-based paint is further improved.
[0021] Preferably, the anti-sewage paint also includes 6-10 parts of aluminum oxide, and the particle size of the aluminum oxide is 30-60 nm.
[0022] Furthermore, the particle sizes of the silicon carbide micropowder and nano silicon dioxide are both 20-40 nm.
[0023] Preferably, the stabilizer is an antioxidant and a light stabilizer, and the weight ratio of the antioxidant to the light stabilizer is 2:1.
[0024] The water-based acrylic polyurethane resin of the present invention can be commercially available water-based acrylic polyurethane resin, and the technical scheme of the present invention can be realized.
[0025] Preferably, the aqueous fluorocarbon emulsion resin is PVDF fluorocarbon resin or FEVE fluorocarbon resin.
[0026] Preferably, in order to further improve the adhesion of the water-based coating, the water-based acrylic polyurethane resin is prepared by the following steps:
[0027] Step 1: prepolymerizing 60-80 parts of diisocyanate, 90-120 parts of polyol, 0.1-5 parts of diol and 10-20 parts of carboxyl diol at 75-95° C. to generate an NCO-containing prepolymer;
[0028] Step 2: cool the NCO-containing prepolymer to 45°C, add 1-20 parts of hydroxy acrylate and heat to 60-65°C for reaction for 4 hours, then add 10-45 parts of chlorine-containing acrylate and appropriate amount of peroxide and react at 70-80°C for 2 hours;
[0029] Step 3: After the copolymerization is completed, 5-15 parts of amine compounds are added to carry out neutralization reaction for 20-30 minutes to obtain water-based acrylic polyurethane;
[0030] Step 4: Add deionized water and emulsify for 45-50 minutes, then evaporate to obtain a water-based acrylic polyurethane emulsion with a solid content of 40-50%.
[0031] The present invention provides a method for preparing a sewage-proof coating, comprising the following steps:
[0032] Step 1: mixing silicon carbide micropowder and nano silicon dioxide to obtain a mixed powder, and then adding an appropriate amount of dispersant and deionized water to the mixed powder for grinding and dispersion to obtain a dispersed mixed powder;
[0033] Step 2: Mix and stir the water-based fluorocarbon emulsion resin, water-based acrylic polyurethane resin, stabilizer, leveling agent, defoamer and the mixed powder to obtain a sewage-proof coating.
[0034] The present invention provides another method for preparing a sewage-proof coating, comprising the following steps:
[0035] Step 1: mixing silicon carbide micropowder, nano silicon dioxide and aluminum oxide to obtain a mixed powder, and then adding an appropriate amount of dispersant and deionized water to the mixed powder for grinding and dispersion to obtain a dispersed mixed powder;
[0036] Step 2: Mix and stir the water-based fluorocarbon emulsion resin, water-based acrylic polyurethane resin, stabilizer, leveling agent, defoamer and the mixed powder to obtain a sewage-proof coating.
[0037] The dispersant is at least one of polyethylene glycol and sodium lauryl sulfate, and the amount of the dispersant is 2-5% of the mixed powder.
[0038] It should be noted that step 1 of the present invention is intended to fully disperse the nano-scale powder, so the amount of deionized water used is based on the prior art and is not particularly limited.
[0039] The present invention also provides an application of the above-mentioned anti-sewage paint, wherein the anti-sewage paint is used as a coating for automotive leather.
[0040] Beneficial Effects
[0041] Compared with the prior art, the present invention has at least the following advantages:
[0042] (1) The present invention discloses a sewage-proof coating, which uses a water-based fluorocarbon emulsion resin as one of the important components, providing the water-based coating with excellent antifouling ability and smoothness;
[0043] (2) Based on the defect of low adhesion of water-based fluorocarbon emulsion resin, the present invention adopts nano-silicon dioxide to increase the adhesion performance of water-based coating. Nano-silicon dioxide particles can produce strong cross-linking effect with polymer molecules. At the same time, due to their small size, they can fill the pores in the coating, making the coating more dense. The dense coating structure improves the adhesion of the coating;
[0044] (3) The present invention produces a synergistic effect through the compounding of nano-silicon dioxide and silicon carbide powder, and uses silicon carbide powder to improve the fluidity of nano-silicon dioxide during the curing process of water-based paint into a coating, so that the ability of nano-silicon dioxide to fill the pores in the coating is further improved, thereby increasing the density of the coating and further improving the adhesion of the water-based paint. DETAILED DESCRIPTION
[0045] The present invention will be further described below in conjunction with the embodiments, but it does not constitute any limitation to the present invention. Any limited number of modifications made within the scope of the claims of the present invention are still within the scope of the claims of the present invention.
[0046] In order to explain the technical content of the present invention in detail, further description is given below in conjunction with the implementation modes.
[0047] In the following examples and comparative examples, the water-based fluorocarbon emulsion resin is FEVE fluorocarbon resin, purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd. (AR solid content 50%); the antioxidant is purchased from BASF Irganox 245-DW provided by Weishi Zhongmingzhi Chemical (Shanghai) Co., Ltd.; the light stabilizer is purchased from TINUVIN 783FDL long-term thermal stabilizer provided by Shanghai Jingyan Chemical Co., Ltd.; the leveling agent SN4034 and defoaming agent SN-6725 are both purchased from Shanghai Shenzhu Chemical Technology Co., Ltd.
[0048] Unless otherwise specified, the waterborne acrylic polyurethane resin in the following examples and comparative examples was purchased from Foshan Shunde Sansheng Trading Co., Ltd., model number WinWin-3041.
[0049] In the following examples and comparative examples, the isophorone diisocyanate and 1,4-butanediol were purchased from Guangzhou Haoyi New Materials Technology Co., Ltd., PCL2000 was purchased from Hubei Langbowan Biotechnology Co., Ltd., dihydroxymethylpropionic acid was purchased from Shandong Xiaoqing New Chemical Co., Ltd., hydroxyethyl acrylate was purchased from Hubei Xinyuhong Biotechnology Co., Ltd., 2-chloroacrylate was purchased from Shanghai Yuanye Biotechnology Co., Ltd., and triethylamine was purchased from Hefeng New Energy Co., Ltd.
[0050] It should be noted that the technical solution of the present invention can be implemented through other commercially available products and is not limited to the above-mentioned manufacturers.
[0051] In the following examples and comparative examples, the particle sizes of the silicon dioxide, silicon carbide powder and aluminum oxide are obtained by sieving to obtain powders with corresponding particle size ranges. This belongs to the prior art and the specific steps are not described in detail.
[0052] Unless otherwise specified, % and part in the present invention refer to percent by weight and part by weight.
[0053] The following examples and comparative examples all adopt the following steps to prepare the anti-sewage coating:
[0054] Step 1: Silicon carbide powder, nano silicon dioxide and aluminum oxide (Example 5) are mixed to obtain a mixed powder, and then a proper amount of dispersant and deionized water are added to the mixed powder for grinding and dispersion to obtain a dispersed mixed powder;
[0055] Step 2: Stir and mix the remaining components with the dispersed mixed powder.
[0056] Example 1
[0057] A sewage-proof coating comprises 20 parts of water-based fluorocarbon emulsion resin, 100 parts of water-based acrylic polyurethane resin, 1 part of silicon carbide micropowder with a particle size of 20-40 nm, 2 parts of nano silicon dioxide with a particle size of 20-40 nm, 0.1 part of light stabilizer, 0.2 part of antioxidant, 0.5 part of leveling agent and 0.5 part of defoamer.
[0058] Example 2
[0059] A sewage-proof coating comprises 40 parts of water-based fluorocarbon emulsion resin, 110 parts of water-based acrylic polyurethane resin, 2 parts of silicon carbide micropowder with a particle size of 20-40 nm, 2 parts of nano silicon dioxide with a particle size of 20-40 nm, 0.1 parts of light stabilizer, 0.2 parts of antioxidant, 0.5 parts of leveling agent and 0.5 parts of defoamer.
[0060] Example 3
[0061] A sewage-proof coating comprises 30 parts of water-based fluorocarbon emulsion resin, 90 parts of water-based acrylic polyurethane resin, 0.5 parts of silicon carbide micropowder with a particle size of 20-40 nm, 1.5 parts of nano silicon dioxide with a particle size of 20-40 nm, 0.1 parts of light stabilizer, 0.2 parts of antioxidant, 0.5 parts of leveling agent and 0.5 parts of defoamer.
[0062] Example 4
[0063] The method is substantially the same as Example 3, except that the water-based acrylic polyurethane resin is prepared by the following steps:
[0064] Step 1: 70 parts of isophorone diisocyanate, 110 parts of PCL2000, 3 parts of 1,4-butanediol and 15 parts of dimethylol propionic acid are prepolymerized at 80° C. to generate an NCO-containing prepolymer;
[0065] Step 2: The NCO-containing prepolymer is cooled to 45°C, 10 parts of hydroxyethyl acrylate is added, the temperature is raised to 63°C and the reaction is carried out for 4 hours, and then 35 parts of 2-chloroacrylate is added, and an appropriate amount of peroxide bis(4-tert-butylcyclohexyl) peroxydicarbonate is added as an initiator and the reaction is carried out at 70°C for 2 hours;
[0066] Step 3: After the copolymerization is completed, 10 parts of triethylamine are added to carry out neutralization reaction for 30 minutes to obtain water-based acrylic polyurethane;
[0067] Step 4: Add deionized water and emulsify for 50 minutes, then evaporate to obtain a water-based acrylic polyurethane emulsion with a solid content of 40%.
[0068] Example 5
[0069] A sewage-proof coating comprises 20 parts of water-based fluorocarbon emulsion resin, 100 parts of water-based acrylic polyurethane resin, 1 part of silicon carbide micropowder with a particle size of 20-40 nm, 2 parts of nano silicon dioxide with a particle size of 20-40 nm, 0.1 part of light stabilizer, 0.2 part of antioxidant, 0.5 part of leveling agent, 0.5 part of defoaming agent, and 8 parts of aluminum oxide with a particle size of 30-60 nm.
[0070] Comparative Example 1
[0071] It is generally the same as Example 3, except that the silicon carbide powder with a particle size of 20-40 nm is replaced by aluminum oxide with a particle size of 20-40 nm.
[0072] Comparative Example 2
[0073] It is generally the same as Example 3, except that the silicon dioxide with a particle size of 20-40 nm is replaced by aluminum oxide with a particle size of 20-40 nm.
[0074] Comparative Example 3
[0075] A sewage-proof coating comprises 30 parts of water-based fluorocarbon emulsion resin, 90 parts of water-based acrylic polyurethane resin, 2 parts of silicon carbide micropowder with a particle size of 20-40 nm, 0.1 parts of light stabilizer, 0.2 parts of antioxidant, 0.5 parts of leveling agent and 0.5 parts of defoamer.
[0076] Comparative Example 4
[0077] A sewage-proof coating comprises 30 parts of water-based fluorocarbon emulsion resin, 90 parts of water-based acrylic polyurethane resin, 2 parts of nano silicon dioxide with a particle size of 20-40 nm, 0.1 parts of light stabilizer, 0.2 parts of antioxidant, 0.5 parts of leveling agent and 0.5 parts of defoamer.
[0078] Performance Testing
[0079] Adhesion test method: According to GB / T9286-2021 cross-cut method
[0080] The adhesion test of the water-based coatings obtained in Examples 1-5 and Comparative Examples 1-4 was performed, and the results are shown in Table 1;
[0081] Table 1 Adhesion results of water-based coatings of application examples 1-3 and application comparative examples 1-2
[0082] Adhesion / Grade Example 1 ≤1.0 Example 2 ≤1.0 Example 3 ≤1.0 Example 4 ≤0 Example 5 ≤1.0 Comparative Example 1 ≤2.0 Comparative Example 2 ≤2.0 Comparative Example 3 ≤2.0 Comparative Example 4 ≤2.0
[0083] According to the results in Table 1, we can see that:
[0084] Due to the addition of water-based fluorocarbon emulsion resin, the adhesion of water-based coatings has been greatly reduced. According to Examples 1-5 of the present invention, the present invention can greatly improve the adhesion performance of water-based coatings by compounding nano-silicon dioxide and silicon carbide powder.
[0085] According to the data comparison between Example 3 and Example 4, it can be seen that the chlorine-containing water-based acrylic polyurethane resin prepared by the present invention can further improve the adhesion performance of water-based coatings.
[0086] According to the data comparison of Example 3 and Comparative Examples 1 and 2, the adhesion performance of the water-based coating obtained by compounding alumina with nano-silicon dioxide or silicon carbide powder, which also has the effect of improving the adhesion of the water-based coating, is not as good as that of the compounding scheme of nano-silicon dioxide and silicon carbide powder, which indicates that the nano-silicon dioxide and silicon carbide powder of the present invention have a synergistic effect of improving the adhesion of the water-based coating. The reason is that the improvement of the adhesion of the water-based coating by alumina is based on the ability of alumina nanoparticles to penetrate into the tiny pores on the surface of the substrate. Through this physical embedding effect, the mechanical bond between the coating and the substrate is enhanced. During this process, although silicon carbide powder improves the fluidity of alumina, the improvement of alumina's adhesion is based on the penetration of alumina into the tiny pores on the surface of the substrate after solidification. Therefore, the improvement of fluidity during the solidification process cannot promote the penetration of alumina nanoparticles after solidification, and there is no synergistic effect between the two. Nano-silicon dioxide particles fill the pores of the coating. Therefore, silicon carbide powder can promote the flow of silicon dioxide during the solidification process to improve the pore filling ability of the coating, thereby further synergistically improving the structural density of the coating and improving adhesion.
[0087] Similarly, according to the data comparison between Example 3 and Comparative Examples 3 and 4, it can be seen that the improvement of the adhesion of the water-based coating is not based on the amount of the adhesion-enhancing filler, but on the synergy of the compounding of nano-silicon dioxide and silicon carbide micropowder.
[0088] The embodiments presented herein are only embodiments selected according to the combination of all possible embodiments. The appended claims should not be limited by the embodiments describing the present invention. Some numerical ranges used in the claims include sub-ranges therein, and the changes in these ranges should also be covered by the appended claims.
Claims
1. A sewage-proof coating, characterized in that: By weight, it includes 20-40 parts of water-based fluorocarbon emulsion resin, 90-110 parts of water-based acrylic polyurethane resin, 0.5-2 parts of silicon carbide micropowder, 0.5-2 parts of nano silicon dioxide, 0.1-0.3 parts of stabilizer, 0.3-0.6 parts of leveling agent, and 0.3-0.6 parts of defoaming agent.
2. The anti-sewage paint according to claim 1, characterized in that: The invention also comprises 6-10 parts of aluminum oxide, and the particle size of the aluminum oxide is 30-60 nm.
3. The anti-sewage paint according to claim 1, characterized in that: The particle sizes of the silicon carbide micropowder and nano silicon dioxide are both 20-40 nm.
4. The anti-sewage paint according to claim 1, characterized in that: The stabilizer is an antioxidant and a light stabilizer, and the weight ratio of the antioxidant to the light stabilizer is 2:
1.
5. The anti-sewage paint according to claim 1, characterized in that: The waterborne acrylic polyurethane resin is prepared by the following steps: Step 1: prepolymerizing 60-80 parts of diisocyanate, 90-120 parts of polyol, 0.1-5 parts of diol and 10-20 parts of carboxyl diol at 75-95° C. to generate an NCO-containing prepolymer; Step 2: cool the NCO-containing prepolymer to 45°C, add 1-20 parts of hydroxy acrylate and heat to 60-65°C for reaction for 4 hours, then add 10-45 parts of chlorine-containing acrylate and appropriate amount of peroxide and react at 70-80°C for 2 hours; Step 3: After the copolymerization is completed, 5-15 parts of amine compounds are added to carry out neutralization reaction for 20-30 minutes to obtain water-based acrylic polyurethane; Step 4: Add deionized water and emulsify for 45-50 minutes, then evaporate to obtain a water-based acrylic polyurethane emulsion with a solid content of 40-50%.
6. A method for preparing a sewage-proof coating as claimed in any one of claims 1, 3, 4 and 5, characterized in that: The steps include: Step 1: mixing silicon carbide micropowder and nano silicon dioxide to obtain a mixed powder, and then adding an appropriate amount of dispersant and deionized water to the mixed powder for grinding and dispersion to obtain a dispersed mixed powder; Step 2: Mix and stir the water-based fluorocarbon emulsion resin, water-based acrylic polyurethane resin, stabilizer, leveling agent, defoamer and the mixed powder to obtain a sewage-proof coating.
7. A method for preparing the anti-sewage coating according to claim 2, characterized in that: The steps include: Step 1: mixing silicon carbide micropowder, nano silicon dioxide and aluminum oxide to obtain a mixed powder, and then adding an appropriate amount of dispersant and deionized water to the mixed powder for grinding and dispersion to obtain a dispersed mixed powder; Step 2: Mix and stir the water-based fluorocarbon emulsion resin, water-based acrylic polyurethane resin, stabilizer, leveling agent, defoamer and the mixed powder to obtain a sewage-proof coating.
8. An application of the anti-sewage coating according to any one of claims 1 to 5, characterized in that: The anti-fouling paint is used as a coating for automotive leather.
Citation Information
Patent Citations
Coating for protecting glass and preparation method thereof
CN106995654A
Stain-resistant high-permeability skin-feeling artificial leather and preparation method thereof
CN112746506A
Wear-resistant high-strength coating and preparation method thereof
CN112760030A
Easy-to-decontaminate and high-wear-resistance synthetic leather for sofas and preparation method thereof
CN113863017A
Stain-resistant and fracture-resistant leather product and preparation method thereof
CN114164679A
Cited By
Stain-resistant and scratch-resistant coating and preparation method thereof
CN120098490A
Macromolecule antiskid technology
CN120554936A